Teaching Speaking to Young Learners Through Storytelling: A Case Study at Primary School - Asih Wahyuni (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
Recently, many primary schools in Indonesia have focused their English language teaching mainly on the students’ ability to speak in English. The primary schools provide students with storytelling which promote their speaking ability. This research aims to portray the storytelling activity in the teaching of speaking that the teacher conducted involving primary school students and to find out the ways how the teacher sets up each of those activities. This study was conducted at one International Primary School in Bandung. The participants of this study were one teacher and the students at the primary 1 up to primary 4 consisting of 44 students. This study employed a case study design. Three instrumentations were used to gain data. The data were analyzed qualitatively in accordance with the two research questions. The validation of the data was conducted through triangulation. The findings revealed that the teacher applied storytelling in the teaching of speaking to the primary schools students (classes 1 up to 4). In conducting the classroom activities, the teacher has provided meaningful and purposeful activities which have followed the three dimensions of learning a target language. The activities to some extent were relevant to young learners’ learning characteristics and their constructed knowledge. Moreover, the research showed that the teacher organized the classroom activities through 1) teaching a class as a whole, 2) organizing group work and 3) organizing oral performance. In organizing the classroom activities, the teacher has promoted the students’ ability to communicate their ideas and thought in English.